A Projec Report on Measuring the Sky : on Computing Data Cubes Via Sky Lining the Muasures - MANISHA KUMARI, SHWETHA B G and SURABHI SANCHITA (2012)
INTERNAL GUIDE: SIMI SARA MANI, CSE DEPT MVJCE
Keywords: Measuring the Sky : on Computing Data Cubes Via Sky Lining the Muasures